Results of experimental research into correlations between hazardous factors of ignition of materials in premises - Pospelov, Boris; Rybka Evgenіy; Meleshchenko, Ruslan; Gornostal, Stella; Shcherbak, Sergey (Eastern-European Journal of Enterprise Technologies, 2017)
We presented results of experimental research into dynamics of hazardous factors of the state of environment, as well as of their autocorrelations and pair correlations in a simulation chamber at various lags for early detection of ignition of combustible materials, such as alcohol, paper, timber and textiles. The study was carried out based of Pearson coefficient of lag correlation that possesses the best interpretability of results. It was found that dynamics of factors of the state of environment in space of the studied factors prior to ignition of materials is locally inhomogeneous and distributed with random transitions between local states. At ignition, in the studied environment, there occurs grouping of its distributed local states depending on material of ignition. It was established that the character of grouping can be used as an indicator of early detection of ignition and identification of the type of combustible material. In this case, early ignition causes a slight increase in constant of time of fluctuations of the studied factors of environment. However, this indicator has insufficient differentiability for early detection of ignitions. A more informative indicator is a degree of mutual correlation of fluctuations of environmental factors at zero lag. It was found that for alcohol, paper, timber and textiles, an effective indicator of early detection of their ignition is coefficient of pair correlation of CO and temperature, the module of which is close to 1, and for textiles – to –1